Potentialities and Impediments to the use of bicycle as a Mean of Transportation in medium-sized cities: A Case Study - Ramos Silva, Malena; Cerqueira do Nascimento Salvalaio, Renata; Gagno de Brito, Jordano Francisco; Engel de Alvarez, Cristina (Guará Journal, 2019)
Non-motorized modes of transportation have emerged as a viable alternative for reducing mobility issues, especially in medium-sized and large cities. This research sought to assess the feasibility of encouraging bicycle use as an alternative transportation option in the city of Vitória, considering the user’s perspective and an assessment of the existing cycling infrastructure. The methodology was structured around an online questionnaire aimed at identifying the main factors that encourage or discourage cycling. The results showed that the presence of cycling infrastructure is the main incentive, followed by economic and health-related factors. The lack of appropriate parking and insecurity also presented themselves as deterrents, especially for daily commutes. As part of the methodology, a seminar was also held with the participation of various segments of society, aiming to broaden the discussion of the results with the community. The data analysis highlighted the viability of non-motorized modes of transport for Vitória, and also identified the need for a strong educational campaign related to the concept of shared roads, as well as the implementation of integrated transport systems, so that streets are not just passageways, but also places of coexistence.